ANALISIS PERAN KOPERASI SIMPAN PINJAM TERHADAP USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KABUPATEN GORONTALO (STUDI PADA KSP “SURYA” UMG) - Nur Eng Mokodompit; Silvoni Rivai (Universitas Muhammadiyah Gorontalo, 2021)
This research aims to: determine and analyze the role of Savings and Loan Cooperatives on Micro, Small and Medium Enterprises (MSMEs) in Gorontalo Regency (Study on KSP